A corpus-based lexical analysis of Indonesian English as a new variety - Endarto, Ignatius Tri (Indonesian Journal of Applied Linguistics, 2020)
The fact that English has been embraced globally by most countries as a second language has prompted its adoption in various media, such as television and newspaper. As a language is adopted by a community of non-native speakers, a new variety of it tends to emerge due to the influence of the linguistic features of those non-native speakers’ arterial language. In Indonesia, where English is spoken as a second or foreign language, there has been a growing number of newspapers published in it. Along with the trend of world Englishes, this raises a question about the possibility of a new variety called Indonesian English. Even though more and more Indonesian teachers start to realize that the goal of English language teaching is no longer to imitate native speakers’ variety, there is still little research done on the topic of Indonesian English. For that reason, by collecting online data from an English language newspaper published in the country, this research identified the lexical characteristics of English variety used by educated Indonesians. It is basically a corpus-based lexical study that employed Corpus Pattern Analysis (CPA) to describe contextualized data gathered from the online newspaper. The focuses of this study were contextual information about loanwords, word meanings, word forms, and collocations, which are pertinent to the Indonesian variety of English. The findings indicated that the lexical characteristics of Indonesian English could be categorized into roughly four groups, namely: Indonesian-origin loanwords, Indonesian English lexicon resulting from semantic shifts and those from morphological shifts, as well as Indonesian English collocations. By doing so, it is expected that this research can provide a theoretical basis for English teachers in Indonesia to embrace an English-as-a-lingua-franca approach in their instructions and anticipate a new variety that might exist in the future: Indonesian English.